2007
DOI: 10.1007/s10734-007-9091-3
|View full text |Cite
|
Sign up to set email alerts
|

Students’ evaluations of the use of e-learning in a collaborative project between two South African universities

Abstract: Online learning is increasingly being used in Higher Education, with a number of advantages to online learning being identified. One of these advantages is the suggestion that online learning provides for equality of opportunity. This article reports on students' evaluations of the use of e-learning in a collaborative project between two South African universities. The results highlighted both positive and negative evaluations of the use of e-learning. The positive aspects identified were that e-learning provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 24 publications
2
12
1
Order By: Relevance
“…This finding is in contrast to the literature, which has identified ICT as offering a means of both improving communication and peer support (Johns, 2003;Rohleder et al, 2007;Mitchell et al, 2001). This highlights the potential to improve this aspect of communication between lecturers and students.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding is in contrast to the literature, which has identified ICT as offering a means of both improving communication and peer support (Johns, 2003;Rohleder et al, 2007;Mitchell et al, 2001). This highlights the potential to improve this aspect of communication between lecturers and students.…”
Section: Discussioncontrasting
confidence: 99%
“…Respondents indicated a preference face-to-face contact as the means by which support could be accessed, which was in agreement with Rohleder et al (2007) who found a similar preference for face-to-face interaction between students and staff in higher education. When considered alongside the findings by Stiller et al (2007), who reported that Australian physiotherapists would prefer a model for clinical education that encouraged more, not less, face-to-face contact time, it seems that ICT should not be used to reduce face-to-face contact time, as has been suggested by Eksteen (2005).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For more information about other aspects of the project and study from the pilot course in 2006, and the courses implemented in 2007 and 2008, see Bozalek et al (2007), Leibowitz et al (2007), Rohleder et al (2008aRohleder et al ( , 2008bRohleder et al ( , 2008c and Swartz et al (2009). For the purposes of this article, 91 final, reflective assignments were analysed (see the Appendix for the details of this assignment).…”
Section: Research Approachmentioning
confidence: 99%